Doxycycline Induced Toxic Epidermal Necrolysis with a Single Dose: A Case Report - Patil, Navin; Palikhey, Anjan; Sah, Chandra Mohan; Gurung, Shanti; Shrestha, Laxmi; Shrestha, Jharana; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2022)
Toxic epidermal necrolysis (TEN) is a rare, life-threatening, severe epidermal necrolytic exanthematous vesicobullous usually drug-induced, mucocutaneous disease characterized by a widespread sloughing of the skin and mucosal surfaces. The most common drugs attributable to cause TEN are antibiotics, anti-inflammatory drugs, chemotherapeutic agents, antivirals, and anticonvulsants. The evolution is accompanied by local as well as general complications which can range from superinfections to multiple organ failure. It is of utmost importance that the treating physician promptly recognizes these conditions, withdraws the offending drug and follows the specific treatment protocol and guidelines (SCORTEN) which together would constitute for a better management and prognosis, with higher rates of survival, and a low prevalence of sequlae. We hereby report the first ever case in Nepal of Doxycycline induced Toxic epidermal necrolysis with a single dose at a tertiary care center.